Separation and preconcentration of riboflavin from human plasma using polythionine coated magnetite/hydroxyapatite nanocomposite prior to analysis by surfactant-enhanced fluorimetry - Farzin, Leila; Shamsipur, Mojtaba (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2017)
The exploration of novel adsorption properties of conductive polymers based on hybridization with biocompatible nanomaterials receives an increasing interest. In this regard, hydroxyapatite (HA) bioceramic is of critical importance mainly owing to its facile synthesis, high surface area, economic and low toxicity in biological environments. In this work, we first prepared and characterized a magnetite/hydroxyapatite (Fe3O4/HA) nanocomposite using the bio-waste chicken eggshell via an attractive green way that involved low cost and irrespective of toxicity. Then, polythionine as a novel class of conductive polymers was in situ coated on the synthesized magnetic bioceramic for the separation and preconcentration of riboflavin (vitamin B2) in human plasma before its fluorimetric determination. Considering the putative role of riboflavin in protecting against cancer and cardiovascular diseases, it is essential to evaluate this vitamin in biological fluids. The described method possesses a linear range of 0.75–262.5μgL−1 (R2=0.9985) and a detection limit of 0.20μgL−1 (signal-to-noise ratio of 3). The relative standard deviations (RSDs) for single-sorbent repeatability and sorbent-to-sorbent reproducibility were less than 4.0% and 7.6% (n=5), respectively. The respective enrichment factor and extraction recovery of the method found to be 35.7 and 98.4%. The analytical performance of method for riboflavin was characterized by good consistency of the results with those obtained by the enzyme-linked immunosorbent assay (ELISA) conventional method (p-value of <0.05). The optimized protocol intended for control determinations of riboflavin in human subjects and is addressed to clinical laboratories. [Display omitted] •This research introduces a modified magnetic bioceramic prepared by wasted eggshell for solid phase extraction of riboflavin from human plasma.•The described method possesses a linear range of 0.75–262.5μgL−1 and a detection limit of 0.20μgL−1.